1961
DOI: 10.1017/s0016672300000537
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in recombination frequencies inNeurospora crassa

Abstract: The available data on heterogeneity in centromere distances for a number of loci in several linkage groups are analysed and interpreted. When the crosses are grouped according to wild-type ancestry, heterogeneity is eliminated in any one group except those which consist of backcrosses or intercrosses. Abbott 4 and 12 are shown to be the source of the heterogeneity while Lindegren and probably Chilton wild strains give consistent, homogeneous distances. In a cross between Abbott 12 and Lindegren wild-types, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Frost (1961) has analysed the consequences of using different stocks of Neurospora crassa and has shown how different genetic backgrounds may have profound effects on recombination frequencies within a given interval. The difficulty in determining the relative positions of ad-5 and chol-2 is most likely due to the fact that they were mutants induced in different wild-type stocks.…”
Section: Mapping the Centromeresmentioning
confidence: 99%
“…Frost (1961) has analysed the consequences of using different stocks of Neurospora crassa and has shown how different genetic backgrounds may have profound effects on recombination frequencies within a given interval. The difficulty in determining the relative positions of ad-5 and chol-2 is most likely due to the fact that they were mutants induced in different wild-type stocks.…”
Section: Mapping the Centromeresmentioning
confidence: 99%
“…The " fine " controls can be recognised in various organisms as heterogeneity in recombination values between the same markers, due to differences between the genotypes involved (the "genetic background "). This type of genetic control has been explored in two fungi in particular, namely Xeurospora crassa (Frost, 1961;Lavigne and Frost, 1964;Smith, 1966Smith, , 1968Catcheside, 1968) and Schizophllum commune (Simchen, 1967;Stamberg, 1968, and personal communication; Simchen and Connolly, 1968) and in both marked variation has been found between different "wild-type " strains. In the latter we have shown that recombination both between Ac.…”
Section: Introductionmentioning
confidence: 99%
“…That similar polygenic control systems operate in fungi has been suggested from findings of extreme heterogeneities in crossing over frequencies for the same markers, when parents with different origins are used (FROST 1961;STADLER and TOWE 1962;NAKAMURA 1966;SIMCHEN and STAMBERG 1969).…”
mentioning
confidence: 80%